HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT DENGAN KESELAMATAN PASIEN DI PUSEKSMAS AMPANA BARAT KABUPATEN TOJO UNA-U NA TAHUN 2025 - Arpin Arpin; Adinda Maharani Jamil Latief; Nur Hamidah; Putri Ayu Tomu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Knowledge and attitudes are the result of cognitive processes through sensing certain objects and social interactions, which shape individual behavior. Patient safety is defined as a condition free from unintentional injury or efforts to prevent injury due to medical procedures and medication errors. This study aims to assess the relationship between nurses' knowledge and attitudes and patient safety at the West Ampana Community Health Center, Tojo Una-Una Regency. This study used a cross-sectional study design with purposive sampling of 30 respondents. The analysis results showed that nurses' knowledge had a significant relationship with patient safety (P = 0.17; P α = 0.05), and nurses' attitudes were also significantly related to patient safety (P = 0.30; P α = 0.05). From the results of the study, it can be concluded that nurses' knowledge and attitudes have a significant effect on patient safety at the West Ampana Community Health Center, Tojo Una-Una Regency in 2025.Keywordsi: IKnowledge, IAttitude, PatientHSafety